PENGEMBANGAN DESAIN DIDAKTIS UNTUK MENGATASI EPISTEMOLOGY OBSTACLE PADA MATERI FUNGSI KOMPOSISI - Milyawati, Lia; Balkist, Pujia Siti; Lukman, Hamidah Suryani (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2022)
The ability and mastery of high school students in mathematics in Indonesia is still low compared to students abroad. The purpose of this study was to determine the students' obstacle epistemology, compile a didactic design based on obstacle epistemology and to find out the results of the didactic design implementation in overcoming the epistemology obstacle in the composition function material. The research method used was Didactical Design Research (DDR) design. The sample of this research was students of class X MIPA SMA Al Umanaa Boarding School, Sukabumi Regency who were taken purposively. The research instrument consisted of 10 descriptive questions which were then analyzed through three stages, namely the prospective, metapedadidactic, and retrospective stages. The results show that the epistemology obstacles that arise include conceptual barriers, procedural obstacles and technical operational obstacles. Students experience conceptual obstacles in the form of not understanding the questions or questions given, not understanding the concept or composition function formula, errors in determining the form of the composition function and how to operate it, while the procedural obstacles that arise are students incorrectly determining the simple form of the function (f / g ) (x), wrong in determining the value of f (x-2), not working on problems and wrong in using arithmetic operations. The obstacles to operational techniques are errors caused by inaccuracy in writing questions and the results of algebraic operations. Based on the epistemology of the obstacle, a didactic design was created and implemented in the classroom. The results of the didactic design implementation show obstacles due to inaccuracy in writing and operating algebraic operations that have not occurred, however, conceptual and procedural obstacles still arise among some respondents.